Development of an English Learning Model for Early Childhood Education (ECE) Using Multimedia-Based Interactive Media - afdhalina, afdhalina; Sridewi, Nurmala (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores effective English language learning strategies for early childhood, emphasizing the importance of early exposure to prepare children for the global era. The research employs a Research and Development (RD) method using the Borg Gall model, which includes five stages: Preliminary Research, Product Development, Product Validation, Product Trial, and Product Dissemination. This approach focuses on designing and implementing an interactive, multimedia-based learning model. The goal is to create a fun, creative, and engaging learning experience through interactive media, helping children better understand and master English. The findings are expected to offer new insights into effective teaching methods that significantly improve children's English language skills.